Clinical characteristics and protective factors in patients with acute myocardial infarction undergoing in-hospital myocardial free wall rupture: a single-center, retrospective analysis. (30th July 2019) - Lou, Bowen; Luo, Yongbai; Hao, Xiang; Sun, Lizhe; Deng, Yangyang; Guo, Manyun; Liu, Junhui; Zhou, Bo; Yuan, Zuyi; She, Jianqing
Abstract : Myocardial free wall rupture (MFWR) refers to laceration of the heart ventricle or atria, which is a rare but fatal complication of acute myocardial infarction (AMI). In this study, we aim to identify the clinical characteristics and protective factors of free wall rupture after myocardial infarction. This is a single-center, retrospective observational analysis. The study screened all patients admitted to the cardiology department of the First Affiliated Hospital of Xi'an Jiaotong University between January 2013 and April 2018. The biochemical, clinical, angiographic and echocardiographic features of these patients were then collected and analyzed. Among the 5946 screened patients with AMI, 23 patients with a diagnosis of MFWR after AMI were enrolled in the present study. 18 (78.3%) patients were diagnosed with acute ST segment elevated myocardial infarction and the remaining 5 (21.7%) have acute non-ST segment elevated myocardial infarction. Early-phase MFWR happened in 12 (52.2%) and late-phase accounted for 8 (34.8%) in total. Late-phase MFWR had lower left ventricle ejection fraction value (45.8%±5.6% vs 63.0±3.8%, p<0.001) as compared with early-phase. Patients who survived from MFWR has higher ACE inhibitor/angiotensin II receptor blocker (ACEI/ARB) and β-blocker coverage in the in-hospital treatment of AMI (ACEI/ARB: 100.0% vs 35.3%, p=0.014; β-blocker: 100.0% vs 47.1%, p=0.048). The present study provides evidence for better understanding of the clinical characteristics and protective functions in MFWR after AMI. Reduced cardiac function is correlated with higher incidence of later phase free wall rupture. Higher ACEI/ARB and β-blocker coverage in the AMI treatment strategy is associated with lower MFWR incidence.